"The Robbed that Smiles Steals Something from the Thief". Issue 84 (July 2016) - Tudball, Dan
Abstract : What of the smile? Is it actually evidence that a crime has been committed: a crime against science, trading, and all that lies in between? We turn to Paul Wilmott, Emanuel Derman, Wim Schoutens, Aaron Brown, and Anatoliy Swischuk for their considered assessment.